PENERAPAN METODE PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN KEAKTIFAN BELAJAR DAN HASIL BELAJAR MATA DIKLAT SISTEM INJEKSI BAHAN BAKAR BENSIN PADA SISWA KELAS XII TKR SMK MUHAMMADIYAH CANGKRINGAN SLEMAN YOGYAKARTA - Dony Borneo; Rabiman Rabiman (Universitas Sarjanawiyata Tamansiswa, 2015)
The purpose of this study (1) to founds progress learning active, couse system injection fuel gasoline for students vocational high scool Muhammadiyah Cangkringan Sleman Yogyakarta for students class XII withmethod inkuiri learning strategy (2) for increase the results of study coorse system injection fuel gasoline for students class XII techniave automotive velicle at SMK Muhammadiyah Cangkringan SlemanYogyakarta with learning inkuiri strategy. Research hipotesis (1) The study applied method inkuiri can increase the result. Learning student in course system injection fuel gasoline an class XII technique engineering vocational high school Muhammadiyah Cangkringan Sleman.This research was apply at vocational high school Muhammadiyah Cangkringan year 2014/2014. Exactly date on march 19 2014 until September 23 2014. Subject topic of discussion in this research is students class XII TKR A 24 totalistudents, type of this research class activity. Technique, observation, documentary. This instrument method experiment was on class XII TKR B vocatioral high school Muhammadiyah Cangkringan Sleman Yogyakarta. The validity question was get frompal product moment korelasion. Based on the result calculated from each of question the cycle was valid. The reability questions was ged alpha abbreviation. Based on analysis was get coefsieent interval at cycle I 0, 3 ,cycle II 0, 3 and cycle III 0,829 has reliable, technique analysis data with quantitative analisis, analisis for student active had include average. Points and reserve power.Based on result research got result (1) the study was use method inkuiri study get progress the student more active in subject system injection fuel gasoline at vocational high school muhammadiyah cangkringan sleman, for class XII tenslas was show from data on cycle I the students has active from percentage cale 37,12 (2) the studies has used method study inkuiri got valid up learning result students in subject system injector fuel gasoline on class XII TKR vocational high school muhammadiyah cangkringan on cycle I scale percentage 70,41 got significant percentage progress on cycle II , scale percentage 7 ,2 . and once again got significant progress on cycle III became 8 ,2 scale percentage.